The Effect of Snakes and Ladder Media in Teams Games Tournament Model on Mathematical Problem Solving Ability - Hanun, Istna Syaikhah; Nugraheni, Nursiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The use of concrete games can increase student enthusiasm and attract students' attention to learning, but many teachers have not yet utilized them as a learning support media.This study was conducted to understand how much influence the Snakes and Ladders media, with the Teams Games Tournament learning model, has on students’ problem-solving abilities. The subjects in this study were grade 5 learners in a state-run primary school in Semarang City, a total of 54 students. This study contributes new insights by analyzing the effect of the tgt-assisted snake and ladder game, which has not been studied before in fifth grade, in different research locations. This current project used a numerical research approach analysis through a quasi-experiment. The results of the study conducted on the treatment group showed an effectiveness value of 65.68. Meanwhile, the control group produced an effectiveness value of 56.59. Based on data analysis using the t-test shows a two-sided significance level (2-tailed) of .000, so H0 was not supported and in favor of H1. So, it shows an influence through the implementation of the Snakes and Ladders media educational tool, along with the TGT instructional approach, to improve the ability of fifth-grade students to understand mathematical problem-solving. Snakes and Ladders media with the TGT cooperative model is also effective for students’ problem-solving abilities. Future research can analyze and calculate the effectiveness of using the snake and ladder media with the tgt model in other subjects more effectively